Impact of wide-spread use of uninterruptible power supplies on Pakistan's power system. (November 2016) - Ahmad, Ali; Saqib, Muhammad Asghar; Rahman Kashif, Syed Abdul; Javed, Muhammad Yaqoob; Hameed, Abdul; Khan, Muhammad Usman
Abstract: The shortage of electrical energy has led Pakistan to a severe energy crisis. A huge mismatch of demand and supply forces the utilities to resort to load-shedding. To overcome this chronic problem the people need to either conserve energy or use some means to fulfil their energy requirements during the load-shedding hours. An easier approach in this regard is the utilization of an uninterruptible power supply (UPS) at user ends. However, due to the absence of any Governmental regulations the Pakistani markets are flooded with low-quality, locally-made UPSs. In this context it was decided to conduct this research, i.e. to explore the impact of these UPSs on the Pakistan's power system. Different types of UPS have been studied in our laboratory. Their charging and discharging processes have been investigated with respect to the harmonics in current and their efficiencies. The UPSs have been estimated to contribute a loss of 410 MW in Pakistan's power system. The cost of the energy lost in these UPSs, from year 2007 to 2013, has been estimated around 1934 million US dollars. The paper finally concludes that there is a need of energy policy in Pakistan to regulate the use of UPSs and related power quality issues. Highlights: The author's analyses commonly used multiple types of UPSs in laboratory. It explores the charging/discharging processes of UPSs with respect to THD and efficiency. Domestic UPSs have significant negative effect on power system in Pakistan. We estimated the UPS losses cost to consumers in Pakistan. Building policy for UPSs efficiency improvements are suggested in conclusion.